Global, regional, and national children and adolescent epilepsy burden, 1990–2021: an analysis based on the global burden of disease study 2021 - Zhenjin Su; Jie Lu; Yuheng Shi; Bin Qi; Zeshang Guo (Annals of Medicine)
Background Epilepsy is a prevalent central nervous system disorder, affecting over 70 million people globally. It ranks fifth among neurological disorders in terms of disease burden. Epilepsy exhibits peak incidence in both childhood and older age, leading to a significant disease burden. This study aims to assess the burden of epilepsy in children and adolescents, analyze its key contributing factors, and identify strategies to mitigate the disease burden.Methods The disease burden of childhood and adolescent epilepsy was analyzed across spatial, temporal, and population levels using data from the Global Burden of Disease 2021 study.Results In 2021, over 8 million children and adolescents worldwide were living with epilepsy. The disease burden in this population is greater in males than in females, with morbidity primarily concentrated in children under 5 years of age and mortality predominantly occurring in adolescents aged 15–19. The current disease burden is strongly correlated with population and epidemiological factors, and while incidence and prevalence are projected to rise, both mortality and Disability-Adjusted Life Years (DALYs) are expected to decrease.Conclusion This study highlights the global changes in the disease burden of epilepsy in children and adolescents. Population factors have been identified as the primary drivers of the increasing burden, while improvements in public health policies and access to treatments have contributed to the decreasing burden. Despite the expected rise in the future incidence, targeted improvements in treatment accessibility and health budget allocations are essential to reduce the long-term burden of epilepsy.